Receptors for Tumor Necrosis Factor-α Play a Protective Role against Obesity and Alter Adipose Tissue Macrophage Status - Pamir, Nathalie (The Endocrine Society, 2009)
TNF-α signals through two receptors, TNFR1 and TNFR2. Our goals were: 1) determine the role of TNFRs in obesity and metabolic disease and 2) investigate whether TNFRs contribute to the link between obesity and adipose tissue macrophage infiltration and polarization. R1(−/−)R2(−/−) (RKO) and wild-type (WT) mice were fed standard chow or a high-fat/high-sucrose diet (HFHS) over 14 wk. Body composition, food intake, and energy expenditure were measured. Oral glucose tolerance and insulin sensitivity tests assessed glucose homeostasis. Adipose tissue and systemic inflammatory status were evaluated by quantifying plasma adipokine levels and macrophage-specific gene expression in fat. RKO mice were heavier (10%) and fatter (18%) than WT controls at 4 wk of age and were 26% heavier and 50% fatter than WT after 14 wk of HFHS diet feeding. Age- and diet-adjusted 24-h oxygen consumption, activity, and respiratory exchange ratio were significantly reduced in RKO mice. Obese RKO mice were markedly insulin resistant, suggesting that intact TNFR signaling is not required for the effect of obesity to impair glucose metabolism. Adipose tissue from HFHS-fed RKO mice exhibited increased macrophage infiltration, but compared with WT mice, macrophage phenotypic markers featured a predominance of antiinflammatory M2 over proinflammatory M1 cells. TNFRs play a physiological role to limit body weight and adiposity by modestly increasing metabolic rate and fatty acid oxidation, and they are required for obesity-induced activation of adipose tissue macrophages. Despite these effects, TNFRs are not required for obesity-induced insulin resistance.